ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN SEKOLAH TINGGI ILMU EKONOMI (STIE) DI WILAYAH KOTA PEKANBARU: ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN SEKOLAH TINGGI ILMU EKONOMI (STIE) DI WILAYAH KOTA PEKANBARU - Gultom, Elida; Nurhayana, Nurhayana (Komunitas Manajemen Kompetitif, 2018)
This study aims to find out how the level of student satisfaction on the performance of lecturers of the College of Economics (STIE) in the city of Pekanbaru. The population in this study were all students who were still active in lectures at the College of Economics in the city of Pekanbaru which consisted of 7 (seven) campuses of the College of Economics (STIE) with a total of 7,367 students. While the sample was taken as many as 500 respondents with sampling techniques using quota sampling and data analysis techniques used were descriptive analysis methods. Based on the results of the study, it was found that the level of student satisfaction on the performance of lecturers of the Economics College in the city of Pekanbaru, in terms of the pedagogic competence of the majority of 63.5% respondents expressed satisfaction with aspects of pedagogic competence. Judging from professional competence most of the respondents 62.3% expressed satisfaction with the aspect of professional competence. Judging from the personality competencies, most respondents 63.7% expressed satisfaction with the aspect of personality competence. And in terms of social competence most of the respondents, namely 59.80% expressed satisfaction with aspects of social competence.